Effect of radiotherapy on T cell and PD-1 / PD-L1 blocking therapy in tumor microenvironment - Chen Chen; Yanlong Liu; Binbin Cui (Taylor & Francis Group, 2021)
Cancer is a worldwide problem that threatens human health. Radiotherapy plays an important role in a variety of cancer treatment methods. The administration of radiotherapy can alter the differentiation pathways and functions of T cells, which in turn improves the immune response of T cells. Radiotherapy can also induce up-regulation of PD-L1 expression, which means that it has great potential for enhancing the therapeutic effect of anti-PD-1/PD-L1 inhibitors and reducing the risk of drug resistance toward them. At present, the combination of radiotherapy and anti-PD-1/PD-L1 inhibitors has shown significant therapeutic effects in clinical tumor research. This review focuses on the mechanism of radiotherapy on T cells reported in recent years, as well as related research progress in the application of PD-1/PD-L1 blockers. It will provide a theoretical basis for the rational clinical application of radiotherapy combined with PD-1/PD-L1 inhibitors.